Think Pair Share technique in teaching speaking skill - Rika Amila Desta (Research in English and Education Journal, 2017)
The objective of this research is to find out whether teaching speaking by using Think Pair Share technique improved students’ speaking skill. This research was conducted at the second grade students of SMP Negeri 14 Banda Aceh. The design of this study was quantitative research. In speaking class, the common problem faced by the students is difficulty in expressing ideas. Through this technique students enter the stage of thinking, pairing, and sharing process. The data were collected by using pre-test and post-test. The instrument of this study was oral test. The result of the test showed that by using speaking assessment which is proposed by Brown (2004). The result of the test was analyzed by using t-test. The calculation result showed that t-score was higher than t-table (3.66 1.68). The result of this study revealed that there was improvement on students’ speaking after taught by using think pair share technique which the mean score of experimental class is 86.4 while the mean score of control class is 72.1. By implementing Think Pair Share, the students are motivated to do the speaking activity during this technique. This method is assumed to give the students an opportunity to practice the target language. It keeps students more active in cooperation and makes them more confident in the class.